1990
DOI: 10.1007/bf01310744
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of feline calicivirus RNA

Abstract: We report here the cloning and 3' sequence determination of feline calicivirus strain F9. Subcloning the 3' terminus enabled the production of strand specific probes for RNA synthesis. We extend the number of virus specific RNAs detected intracellularly to 8, and show that numbers 1-5 are represented as negative strands which may serve as templates in the synthesis of these RNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
29
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 21 publications
2
29
0
1
Order By: Relevance
“…The predicted protein shows 90-94 % identity at the amino acid sequence level amongst five different FCV strains (Seal et al, 1993). A homologous small ORF is also present at the 3" end of NV, RHDV, VESV and SMSV (Carter, 1990;Meyers et al, t991;Neill, 1992;Jiang et al, 1993) and is conserved at the amino acid sequence level within members (Milton et al, 1992;Neill, 1992;Seal et al, 1993). The conservation of this hypothetical polypeptide argues that it plays a functional role.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…The predicted protein shows 90-94 % identity at the amino acid sequence level amongst five different FCV strains (Seal et al, 1993). A homologous small ORF is also present at the 3" end of NV, RHDV, VESV and SMSV (Carter, 1990;Meyers et al, t991;Neill, 1992;Jiang et al, 1993) and is conserved at the amino acid sequence level within members (Milton et al, 1992;Neill, 1992;Seal et al, 1993). The conservation of this hypothetical polypeptide argues that it plays a functional role.…”
mentioning
confidence: 98%
“…The template RNA for the production of ORF3 is uncertain. It has been suggested that a shorter subgenomic RNA of 0.5 kb may be present in FCV-infected cells (Carter, 1990) which could serve as the template. However, when oligo(dT)-selected FCV RNA was translated in RRL and the products immunoprecipitated with anti-ORF3 antiserum (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The most abundant transcript is a 2.4 kb subgenomic RNA which can be detected as early as 2 h p.i. (Neill & Mengeling, 1988;Carter, 1990) and has been identified as the transcript encoding the viral capsid protein (Neill et al, 1991). The capsid protein gene has been sequenced for the CFI/68 isolate (Neill et al, 1991), the F4 isolate (Toya et al, 1991b) and F9 isolate (Carter et al, 1992a, b) of FCV.…”
mentioning
confidence: 99%